Structural and Magnetic Properties of Barium-Strontium-Hexaferrite Material Ba0.6Sr0.4Fe10-xCoxMnTiO19 (x = 0.5; 1.0; and 1.5) as Microwave Absorbers - Yohanes Edi Gunanto; Maykel Manawan; Maya Puspitasari Izaak; Henni Sitompul; Yunasfi Yunasfi; Wisnu Ari Adi (Directorate for Research and Community Services (LPPM) ITB, 2024)
We discuss the structure properties of Ba0.6Sr0.4Fe10-xCoxMnTiO19(BSFCMTO) for x = 0.5, 1.0, and 1.5 that influence its magnetic properties as a microwave absorber. A solid-state reaction method using high-energy milling was used to synthesize hexaferrite. There were no structural changes when the Co2+ ion was substituted for the Fe3+ ion; the structures of all samples were hexagonal and the space group was P63/mmc. The surface morphology had heterogeneous particles with a size of 300 to 600 nm. The magnetic properties tended to decrease with an increasing number of Co2+ ion substitutions. The reflection loss (RL) had a minimum value of -14.89 dB. This value was reached at a frequency of 10.96 GHz and had a bandwidth at 1.24 GHz with a sample thickness of 1 mm in the Ba0.6Sr0.4Fe9.9Co0.1MnTiO19 sample.